Experimental Study on Bearing Capacity of Corroded Reinforced Concrete Arch Considering Material Degradation - Xin, Jingzhou; Wang, Jieyun; Liu, Zengwu; You, Xing; Zhou, Jianting (Frontiers in Materials, 2022)
To study the bearing capacity of corroded reinforced concrete (RC) arch and analyze the deterioration mechanism of in-service RC arch bridge, the deterioration simulation under the coupling effect of environment and load was performed by employing non-immersion energization and considering the dead load on the arch, the single point loading test of the arch models were carried out, the crack development, structural deformation and ultimate bearing capacity of corroded RC arch under service stress were studied, the failure mode of the corroded arch was explored, and the bearing capacity prediction model considering the dual deterioration effects of reinforcement corrosion deterioration and arch axis deterioration was established. Results indicated that the spacing of cracks caused by loading of non-corroded arch was more uniform, the number and distribution range of load-induced cracks in corroded arch was smaller, while the maximum crack width was larger. Corrosion significantly reduced the strength of arch rib, for the deteriorated arch with a corrosion rate of 7.62%, the cracking load and the bearing capacity decreased by 28.57% and 9.84%, respectively. The corrosion weakened the structural stiffness, while it does not convert the failure mode of the arch. Only considering section resistance degradation may underestimate the damage effect of the corrosion on arch structure.